Method for preparing array carbon nanotubes by taking LNG (liquefied natural gas) as carbon source
By using LNG as a carbon source and preparing catalysts based on layered compounds and iron and nickel active substances, the problems of high production costs and low magnifications of existing array carbon nanotubes are solved, and low cost, high magnifications and high quality carbon is achieved Nanotube preparation.
Patent Information
- Application Number
- CN202411996313.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing methods for preparing array carbon nanotubes are expensive, with low or unstable production rates and low production quality.
Liquefied natural gas (LNG) is used as the carbon source, and catalysts are prepared by ion exchange method based on layered compounds as support and iron and nickel as active substances, and array carbon nanotubes are prepared by catalytic cracking.
The raw material cost is reduced, the production rate and production quality of carbon nanotubes are improved, and the prepared carbon nanotubes have good dispersion and conductivity.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanotube preparation, in particular to a method for preparing array carbon nanotubes by using LNG as a carbon source. Background Art
[0002] Carbon nanotubes (CNTs) are a one-dimensional quantum material with a special structure. They are lightweight, have perfectly connected hexagonal structures, and have excellent optical, thermal, acoustic, mechanical, electrical and chemical properties. Due to their excellent conductivity, carbon nanotubes are currently widely used in lithium-ion batteries and also have great application prospects in sodium-ion batteries.
[0003] Carbon nanotubes can be divided into entangled CNTs and arrayed CNTs according to their aggregation state. Generally speaking, CNTs grown on disorderly stacked catalysts present a certain agglomeration structure, severe entanglement, and disordered arrangement, which has an adverse effect on subsequent dispersion and other processing processes; under certain conditions, CNTs are orderly oriented and arranged in parallel, which is arrayed CNTs. Currently, carbon nanotubes on the market are mainly prepared by chemical vapor deposition (CVD), in which carbon source is an important part of CVD. The carbon source that can be used for industrial preparation of arrayed CNTs is mainly propylene. For example, patent CN115805076A "Catalyst and preparation method thereof, arrayed carbon nanotubes and preparation method thereof" discloses a catalyst preparation method in which a soluble active component, a soluble carrier component containing a carrier element, and a soluble complexing agent are directly dissolved in water to form a catalyst precursor, and the catalyst is calcined at 500-900°C for 10min-4h, and propylene is used as a carbon source for catalytic cracking to prepare arrayed CNTs. Patent CN 114632521 A "Preparation method of vermiculite-based catalyst and carbon nanotube preparation method, as well as catalyst and carbon nanotube prepared therefrom" provides a catalyst prepared by ion exchange method using pretreated vermiculite as carrier, iron nitrate, aluminum nitrate, magnesium nitrate, ammonium heptamolybdate, and citric acid as active substances, and propylene as carbon source to prepare array CNTs. The multiple of array CNTs in this patent is relatively low. There are also reports using ethylene as carbon source, such as patent CN111247094 A "Controlled height carbon nanotube array" discloses a method for preparing highly controllable array CNTs using layered minerals as carriers, calcined after soaking in Fe, Co, and Ni active solutions, and ethylene as carbon source. Its loading method is an excessive impregnation method, and the amount of active substances adsorbed by the carrier cannot be accurately controlled, which leads to unstable multiple of CNTs; the patent does not involve the multiple of ethylene cracking of the prepared catalyst.
[0004] The above technologies all use propylene or ethylene as carbon source to prepare carbon nanotubes. However, the current market prices of propylene and ethylene are high, which makes the production cost of carbon nanotubes high, and the production rate is low or unstable. The array length of CNTs currently available on the market is relatively long and the specific surface area is relatively large (>200m 2 / g), which is not conducive to the subsequent dispersion of the conductive paste, and the prepared conductive paste has a high viscosity. In addition, the carbon nanotubes prepared by the catalyst using nickel as the active substance at this stage are generally thick tubes (tube diameter is about 30-100nm). Therefore, the production quality of carbon nanotubes at this stage is also low. Summary of the invention
[0005] In view of the shortcomings of existing methods for preparing array carbon nanotubes, such as high cost, low or unstable production rate, and low production quality, the present invention provides a method for preparing array carbon nanotubes using LNG as a carbon source, which has low cost, high production rate, and good production quality.
[0006] A method for preparing array carbon nanotubes using LNG as a carbon source, characterized in that: based on a layered compound as a carrier, a catalyst is prepared by an ion exchange method using iron and nickel as active substances, and liquefied natural gas LNG is used as a carbon source for catalytic cracking to prepare array CNTs, which comprises the following steps: S1: Carrier pickling; Carrier pickling includes the following steps: A1: Weigh the layered compound into a beaker, add dilute nitric acid solution and stir; A2: Heat the beaker and keep the temperature constant to react and obtain an acid-washed carrier; A3: Filter or centrifuge the acid-washed carrier, wash it with deionized water until it is weakly acidic or neutral, and continue to filter or centrifuge to maintain the moisture content of the acid-washed carrier; S2: Catalyst preparation; the method for preparing the catalyst comprises the following steps: B1: Weigh a soluble metal salt and dissolve it in deionized water to form an active metal solution A; B2: Weigh the additive metal salt and dissolve it in deionized water to form solution B; B3: Continue stirring the solution A, add the solution B into the solution A, and continue stirring until the solution becomes clear and transparent, which is marked as solution C; B4: Weigh the acid-washed carrier and place it in a high-pressure reactor, add the solution C and stir evenly, then place it in a resistance furnace to heat up, exhaust steam until slight yellow smoke emerges, stop the reaction, and form a catalyst precursor; B5: taking out the catalyst precursor in the high-pressure reactor, and calcining the catalyst precursor at high temperature to obtain a crude catalyst; B6: Screening the crude catalyst to obtain the target catalyst; S3: LNG cracking; The method of LNG cracking comprises the following steps: C1: weigh the target catalyst for use; C2: The fluidized bed reactor is heated up and N2 is introduced to remove the residual oxygen in the fluidized bed reactor. C3: adding a catalyst into the reactor, sealing the fluidized bed reactor, and after the temperature in the fluidized bed reactor is stabilized, introducing a reducing gas to carry out a reduction reaction; C4: Switch to cracking gas for cracking reaction; C5: After the reaction is completed, heating is stopped and N2 is introduced to replace the cracking gas until the temperature drops to room temperature to obtain array CNTs.
[0007] It is further characterized by: In A1, the layered compound includes at least one or any combination of vermiculite, mica, saponite or montmorillonite, and the concentration of the dilute nitric acid solution is 0.5-0.8 mol / L; In A2, the beaker is heated to 70-80°C and the temperature is kept constant for 0.5-3h; in A3, the moisture content of the acid-washed carrier is maintained between 56% and 70%; In B1, the soluble metal salt includes a soluble nickel salt, a soluble iron salt and a soluble aluminum salt; the soluble nickel salt includes at least one or any combination of nickel nitrate, nickel acetate, nickel chloride and nickel sulfate; the soluble iron salt includes at least one or any combination of ferric nitrate, ferric acetate, ferric chloride and ferric sulfate; the soluble aluminum salt includes at least one or any combination of aluminum nitrate, aluminum chloride and aluminum sulfate; the concentration of the soluble metal nickel salt is 1.0-2.5 mol / L, the concentration of the soluble metal iron salt is 1.0-2.5 mol / L, and the concentration of the soluble metal aluminum salt is 0.5-1.0 mol / L; In B2, the auxiliary metal salt includes at least one or any combination of ammonium molybdate, ammonium metatungstate, lanthanum nitrate or ammonium metavanadate, and the molar ratio of the total amount of the auxiliary metal to the active substance metal is between 0.01-0.15; In B4, the mass ratio of the pickled carrier to the solution C is 1:3-5, and the temperature of the resistance furnace is 600-700°C; zirconium beads are added inside the high-pressure reactor to prevent boiling during the heating process; the mass ratio of the zirconium beads to the carrier is 1:20; When the batch size of the target catalyst is less than 10 kg, the following steps are also included before step B5: B5': After the autoclave is cooled to room temperature, the catalyst precursor in the autoclave is taken out and placed in a halogen moisture analyzer for moisture testing, and the moisture content is controlled at 15-25%; In B6, the catalyst precursor is calcined at 400-700° C. for 2-8 hours, and the particle size of the target catalyst obtained after screening is 60-120 mesh; the catalyst with a particle size greater than 120 mesh obtained after screening is used for cracking LNG in a mobile fixed bed; In C2, the fluidized bed reactor is heated to 650-700°C, and 300L / h N2 is introduced for 4-6min; in C3, the reducing gas includes a mixed gas of 270L / h N2 and 30L / h H2, and the reduction reaction time is 0-20min; in C4, the cracking gas includes a mixed gas of 210L / h LNG and 60L / h H2, and the cracking reaction time is 0.5-2h.
[0008] After adopting the above method of the present invention, the price of LNG is lower than that of propylene and ethylene, so the preparation of array CNTs using LNG as a carbon source reduces the cost of raw materials. The auxiliary metal salt can form a co-solvent with the active metal in the catalyst in the catalyst cracking LNG reaction, which is beneficial to reduce the particle size of the catalyst, improve the distribution of the active metal on the carrier, and reduce the agglomeration of the active metal nickel-iron particles, thereby activating the catalyst and improving the production rate and production quality of carbon nanotubes. Carrier pickling can etch impurities in the carrier, thereby improving the effect of the carrier carrying the catalyst and ensuring a higher production rate. The mass ratio of the pickled carrier to solution C is 1:3-5, which can prevent the increase of agglomeration of active metal particles and reduce the catalyst cracking performance, further improving the production rate and production quality of carbon nanotubes. When making the catalyst precursor, the reaction is stopped when a slight yellow smoke appears when the steam is discharged from the reactor. When this phenomenon occurs, the catalyst precursor with the water content suitable for the present invention can be obtained, which provides a convenient way to quickly control the water content of the catalyst precursor. It is especially suitable for preparing catalysts in large quantities. It is not necessary to measure the water content of the catalyst precursor, saving time, equipment and labor costs, and further ensuring a higher production rate and low cost. The target catalyst with a particle size of 60-120 mesh can crack LNG in a fluidized bed to produce carbon nanotubes, and the catalyst with a particle size greater than 120 mesh can crack LNG in a mobile fixed bed to produce carbon nanotubes, making full use of catalysts of various particle sizes to reduce the preparation cost of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a TEM electron microscope image of the average tube diameter of 11 nm from Example 1; Figure 2 This is a SEM electron microscope image of the average tube diameter of 11 nm from Example 1; Figure 3 This is a TEM electron microscope image from Example 5, with an average tube diameter of 13.7 nm. DETAILED DESCRIPTION
[0010] The present invention provides a method for preparing array carbon nanotubes using LNG as a carbon source, which is based on a layered compound as a carrier, iron and nickel as active substances, and a catalyst prepared by an ion exchange method, and LNG is used as a carbon source for catalytic cracking to prepare array CNTs, which comprises the following steps: S1: Carrier pickling; Carrier pickling includes the following steps: A1: Weigh a layered compound and place it in a beaker, add a dilute nitric acid solution with a concentration of 0.5-0.8 mol / L and stir; the layered compound includes at least one or any combination of vermiculite, mica, saponite or montmorillonite; A2: Heat the beaker to 70-80°C and keep the temperature constant for 0.5-3h to react.
[0011] A3: After the reaction is completed, the acid-washed carrier is filtered or centrifuged, and washed with deionized water until it is weakly acidic or neutral. The filtration or centrifugation is continued until the moisture content of the acid-washed carrier is maintained between 56% and 70%.
[0012] In this step, when the concentration of dilute nitric acid is lower than 56%, the impurities inside the layered compound are not sufficiently etched. + Mg contained in the layered compound 2+ 、Al 3+ , Ca 2+ The ion exchange capacity is weakened, resulting in the weakening of the performance of the subsequent catalyst preparation for cracking LNG; when the concentration of dilute nitric acid is higher than 70%, it is easy to cause the internal layered structure of the layered compound to collapse and a large amount of metal cations to be lost, which is not conducive to the subsequent catalyst preparation.
[0013] S2: Catalyst preparation; Catalyst preparation comprises the following steps: B1: Weigh a soluble metal salt and dissolve it in deionized water to form an active metal solution A; the soluble metal salt includes a soluble nickel salt, a soluble iron salt and a soluble aluminum salt; the soluble nickel salt includes at least one or any combination of nickel nitrate, nickel acetate, nickel chloride and nickel sulfate; the soluble iron salt includes at least one or any combination of ferric nitrate, ferric acetate, ferric chloride and ferric sulfate; the soluble aluminum salt includes at least one or any combination of aluminum nitrate, aluminum chloride and aluminum sulfate; the concentration of the soluble metal nickel salt includes 1.0-2.5 mol / L, the concentration of the soluble metal iron salt is 1.0-2.5 mol / L, and the concentration of the soluble metal aluminum salt is 0.5-1.0 mol / L; B2: Weigh an auxiliary metal salt and dissolve it in deionized water to form solution B; in B2, the auxiliary metal salt includes at least one or any combination of ammonium molybdate, ammonium metatungstate, lanthanum nitrate or ammonium metavanadate, and the molar ratio of the total amount of auxiliary metal to the active substance metal is between 0.01-0.15; The auxiliary metal salt plays a major role in assisting the activation of the catalyst in the catalytic cracking of LNG. The melting point of the auxiliary metal salt is relatively high, above 2000°C. It can form a co-solvent with the active metal in the catalyst, which is beneficial to reduce the particle size of the catalyst, improve the distribution of the active metal on the carrier, and reduce the agglomeration of the active metal nickel-iron particles. When the molar ratio of the total amount of the auxiliary metal to the active substance metal is lower than 0.01, the auxiliary metal cannot play a role in assisting the activation of the catalyst due to its low content. When the molar ratio of the total amount of the auxiliary metal to the active substance metal is higher than 0.15, the auxiliary metal competes with the active metal for the reactive active sites due to its high content. Since the auxiliary metal itself has no activity or extremely low activity, the active sites of the catalyst are reduced and the ability to crack carbon sources is reduced.
[0014] B3: Continuously stir solution A, add solution B into solution A, and continue stirring until the solution is clear and transparent, marked as solution C; when the additive solution is added to the metal active solution, the cracking rate of the catalyst can be increased, and the catalyst cracking performance is increased by 15% compared with when the metal active solution is added to the additive solution.
[0015] B4: Weigh the acid-washed carrier and place it in a high-pressure reactor. Add a small amount of 3mm zirconium beads inside the reactor to prevent boiling during heating; the mass ratio of zirconium beads to carrier is 1:20; add solution C and stir evenly, then place it in a resistance furnace at 600-700℃ to heat it up, exhaust steam until slight yellow smoke comes out, and stop the reaction; The mass ratio of the acid-washed carrier to solution C is 1:3-5. When the mass ratio of the acid-washed carrier to solution C is lower than 1, the ion exchange time between the carrier and the solution is too short, resulting in some active metals not completely entering the interior of the carrier and concentrating on the surface of the carrier. In the subsequent roasting process, the active metal particles are agglomerated and increased, reducing the catalyst cracking performance; when the mass ratio of the acid-washed carrier to solution C is higher than 3.5, on the one hand, the active metal content is too high and agglomeration will also occur on the carrier surface. On the other hand, due to the increase in solution, the preparation time of the catalyst increases, and the required heating energy increases accordingly, that is, the preparation cost of the catalyst increases.
[0016] The steam is exhausted until a slight yellow smoke emerges, and the reaction is stopped, because at this stage the water vapor in the reactor has been basically drained, and the ion exchange process between the active substance in the solution and the carrier has been completed. The appearance of slight yellow smoke indicates that a small amount of nitrate has decomposed inside the catalyst to produce nitrogen oxides (yellow smoke); if the heating is continued, the metal nitrate will decompose and produce a large amount of nitrogen oxides; in addition, when this phenomenon occurs, the catalyst precursor with the water content suitable for the present invention can be obtained. This provides a convenient way to quickly control the water content of the catalyst precursor, especially when preparing a large batch of catalysts with a mass greater than 10kg, and B5' can be omitted.
[0017] B5': After the autoclave is cooled to room temperature, the catalyst precursor in the autoclave is taken out and placed in a halogen moisture analyzer for moisture testing. The moisture content is controlled at 15-25%; B5: Take out the catalyst precursor in the high-pressure reactor, and calcine the catalyst precursor at 400-700° C. for 2-8 hours to obtain a crude catalyst; The catalyst precursor is selected as the loose carrier in the reactor, rather than the contact part between the inner wall of the reactor and the carrier. The main reason is that the contact part between the inner wall of the reactor and the carrier is easy to agglomerate under high temperature conditions, resulting in inaccurate moisture measurement. At the same time, the performance of this part of the catalyst in cracking LNG is poor.
[0018] The particle size of the target catalyst is 60-120 meshes. Particle sizes that are too large or too small are not conducive to fluidized bed production. The remaining catalysts larger than 120 meshes can crack LNG in a mobile fixed bed. The resulting carbon nanotubes have the same performance, making full use of the catalyst to reduce the catalyst preparation cost.
[0019] B6: Screening the crude catalyst to obtain the target catalyst. The particle size of the target catalyst is 60-120 mesh. Too large or too small a particle size is not conducive to fluidized bed production. The remaining catalysts larger than 120 mesh can be used to crack LNG in a mobile fixed bed. The obtained carbon nanotubes have the same performance, making full use of the catalyst to reduce the preparation cost of the catalyst. The technology of using a 120-mesh catalyst to crack LNG in a mobile fixed bed is prior art and will not be elaborated on here.
[0020] S3: LNG cracking; LNG cracking includes the following steps: C1: weigh 1.0 g of target catalyst for use; C2: The fluidized bed reactor was heated to 650-700°C and 300 L / h N2 was introduced for about 5 min to remove the residual oxygen in the quartz reactor; C3: Then, the target catalyst is added into the reactor, the reactor is sealed, and after the temperature in the reactor is stabilized, reducing gas is introduced for reduction for 0-20 minutes; the reducing gas includes a mixture of 270L / h N2 and 30L / h H2; C4: Switch to cracking gas cracking reaction time of 0.5-2h; cracking gas includes 210L / h LNG and 60L / h H2 mixed gas; C5: After the reaction is completed, heating is stopped and N2 is introduced to replace the cracking gas until the temperature drops to room temperature to obtain array CNTs.
[0021] Example 1 S1: carrier acid washing; A1: Weigh 500g of vermiculite and place it in a 2000mL beaker, add 1L of 0.5mol / L dilute nitric acid solution and stir, heat the beaker to 75℃ and keep the temperature constant for 2h. After the reaction is completed, filter or centrifuge the carrier, wash it with deionized water until it is weakly acidic or neutral, and continue to filter until the moisture content of the carrier remains between 60% and 70%.
[0022] Catalyst preparation; B1 Weigh 140.4 g nickel nitrate hexahydrate, 180 g iron nitrate nonahydrate and 85.4 g aluminum nitrate nonahydrate into a 1L beaker filled with 260 ml deionized water, and continue stirring until dissolved into a transparent solution, marked as active metal solution A; B2 Weigh 15g of ammonium molybdate and dissolve it in 170ml of deionized water to form solution B; B3: Continue stirring solution A, add solution B into solution A, and continue stirring until the solution is clear and transparent, which is marked as solution C; B4 Weigh 200g of the acid-washed carrier and place it in a high-pressure reactor, add solution C and stir evenly, then place it in a resistance furnace at 650℃ to heat it up, exhaust steam until yellow smoke comes out, and stop the reaction; B5 After the autoclave is cooled to room temperature, the catalyst precursor in the autoclave is taken out and placed in a halogen moisture analyzer for moisture testing; B6: The catalyst precursor is calcined at 500°C for 5 hours, and sieved using 60-mesh and 120-mesh sieves to obtain the target catalyst.
[0023] Cracking LNG; C1: Weigh 1.0 g of target catalyst for use.
[0024] C2: The fluidized bed reactor was heated to 680°C and 300 L / h N2 was introduced for 5 min to remove the residual oxygen in the fluidized bed reactor:.
[0025] C3: Add the catalyst into the fluidized bed reactor, seal the fluidized bed reactor, and after the temperature in the reactor stabilizes, introduce reducing gas (mixed gas of 270L / h N2 and 30L / h H2) for 0min reduction; C4: Switch to cracking gas (210L / h LNG and 60L / h H2 mixed gas) with a cracking reaction time of 1h.
[0026] C5: After the reaction is completed, heating is stopped and N2 is introduced to replace the cracking gas until the temperature drops to room temperature to obtain array CNTs.
[0027] Example 2 is prepared in the same manner as Example 1, except that the ammonium molybdate in the catalyst preparation is changed to ammonium metatungstate.
[0028] Example 3 is prepared in the same manner as Example 1, except that ammonium molybdate in the catalyst preparation is replaced by lanthanum nitrate.
[0029] Example 4 is prepared in the same manner as Example 1, except that the ammonium molybdate in the catalyst preparation is changed to ammonium metavanadate.
[0030] Example 5 The preparation method is the same as that of Example 1, except that the masses of nickel nitrate hexahydrate, iron nitrate nonahydrate and aluminum nitrate nonahydrate in the catalyst preparation are changed to 190.5 g, 195.5 g and 95 g respectively.
[0031] Example 6 In 1 liter of dispersant, 5g of dispersant polyvinyl pyrrolidone (PVP) and 375g of N-methylpyrrolidone were added thereto and dispersed at 2000rpm. After uniform dispersion, 1500g of zirconium beads and 20g of carbon nanotubes prepared in Example 1 were added, and stirring was continued at high speed (4000rpm) for 5.5h. The test sample was then taken out for testing every 30 minutes. The Hegman scale reading was used, and when the reading was less than 10 microns, the material was discharged, and the discharge viscosity of the slurry was measured at 25°C using a Brookfield viscometer. The above-dispersed carbon nanotube slurry was used to manufacture a lithium ion cathode electrode. Li(NiCoMn)O2 mixed metal oxide (NCM) was used as a cathode material. A cathode slurry containing NCM, carbon nanotubes, PVP and polyvinylidene fluoride (PVDF) was prepared by mixing appropriate amounts of NCM, carbon nanotube slurry and PVDF together with N-methylpyrrolidone in a high-speed mixer. The slurry coating was scraped off on the Al foil using a scraper, and then dried and compressed for subsequent measurement. The final carbon nanotube slurry had a solid content of 6.51%, a viscosity of 130mpa·s, 1208mpa·s after one week, and 5700mpa·s after four months. The resistivity of the electrode sheet prepared with NCM as the cathode material was 5.39Ω·cm.
[0032] Comparative Example 1 was prepared in the same manner as in Example 1, except that the reduction time during the catalyst cracking LNG was 10 min.
[0033] Comparative Example 2 was prepared in the same manner as in Example 1, except that active metal solution A was added to solution B during the catalyst preparation process.
[0034] Table 1 Summary of corresponding carbon tube data in the examples of preparing carbon tubes Specific instructions Figure 1 It shows that the carbon tubes prepared by the nickel-iron catalyst of the present invention have a relatively thin tube diameter, with an average tube diameter of 11 nm, and more than half of the tubes have a diameter within 10 nm. Figure 2It shows that the growth mode of the carbon nanotubes prepared by the catalyst of the present invention is vertical growth, and the tube length is between 20-50 μm. Figure 3 It shows that increasing the nickel content in the catalyst will increase the average diameter of the obtained carbon nanotubes.
[0035] From Table 1, Figure 1 , Figure 2 , Figure 3 It can be seen that the array CNTs carbon source prepared by the present invention has low cost, high carbon yield (>20), good dispersibility, good tube diameter uniformity (average tube diameter is about 11nm), moderate array tube length (20-50μm), low specific surface area (150-200m2 / g), moderate tap density (0.03-0.06g / cm3), good conductivity (powder resistivity is between 10-20mΩ·cm), the prepared high solid content slurry has low viscosity and extremely high production quality.
Claims
1. A method for preparing array carbon nanotubes using LNG as a carbon source, characterized in that: The method is based on layered compounds as carriers, uses iron and nickel as active substances to prepare catalysts through ion exchange, and uses liquefied natural gas LNG as a carbon source to catalytically crack and prepare array CNTs, which includes the following steps: S1: Carrier pickling; Carrier pickling includes the following steps: A1: Weigh the layered compound into a beaker, add dilute nitric acid solution and stir; A2: Heat the beaker and keep the temperature constant to react and obtain an acid-washed carrier; A3: Filter or centrifuge the acid-washed carrier, wash it with deionized water until it is weakly acidic or neutral, and continue to filter or centrifuge to maintain the moisture content of the acid-washed carrier; S2: Catalyst preparation; the method for preparing the catalyst comprises the following steps: B1: Weigh a soluble metal salt and dissolve it in deionized water to form an active metal solution A; B2: Weigh the additive metal salt and dissolve it in deionized water to form solution B; B3: Continue stirring the solution A, add the solution B into the solution A, and continue stirring until the solution becomes clear and transparent, which is marked as solution C; B4: Weigh the acid-washed carrier and place it in a high-pressure reactor, add the solution C and stir evenly, then place it in a resistance furnace to heat up, exhaust steam until slight yellow smoke emerges, stop the reaction, and form a catalyst precursor; B5: taking out the catalyst precursor in the high-pressure reactor, and calcining the catalyst precursor at high temperature to obtain a crude catalyst; B6: Screening the crude catalyst to obtain the target catalyst; S3: LNG cracking; The method of LNG cracking comprises the following steps: C1: weigh the target catalyst for use; C2: The fluidized bed reactor is heated up and N2 is introduced to remove the residual oxygen in the fluidized bed reactor. C3: adding a catalyst into the reactor, sealing the fluidized bed reactor, and after the temperature in the fluidized bed reactor is stabilized, introducing a reducing gas to carry out a reduction reaction; C4: Switch to cracking gas for cracking reaction; C5: After the reaction is completed, heating is stopped and N2 is introduced to replace the cracking gas until the temperature drops to room temperature to obtain array CNTs.
2. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 1, characterized in that: In A1, the layered compound includes at least one or any combination of vermiculite, mica, saponite or montmorillonite, and the concentration of the dilute nitric acid solution is 0.5-0.8 mol / L.
3. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 1, characterized in that: In A2, the beaker is heated to 70-80°C and the temperature is kept constant for 0.5-3h.
4. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 1, characterized in that: In A3, the moisture content of the acid-washed carrier is maintained between 56% and 70%.
5. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 1, characterized in that: In B1, the soluble metal salt includes a soluble nickel salt, a soluble iron salt and a soluble aluminum salt; the soluble nickel salt includes at least one or any combination of nickel nitrate, nickel acetate, nickel chloride and nickel sulfate; the soluble iron salt includes at least one or any combination of ferric nitrate, ferric acetate, ferric chloride and ferric sulfate; the soluble aluminum salt includes at least one or any combination of aluminum nitrate, aluminum chloride and aluminum sulfate; the concentration of the soluble metal nickel salt is 1.0-2.5 mol / L, the concentration of the soluble metal iron salt is 1.0-2.5 mol / L, and the concentration of the soluble metal aluminum salt is 0.5-1.0 mol / L.
6. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 5, characterized in that: In B2, the auxiliary metal salt includes at least one or any combination of ammonium molybdate, ammonium metatungstate, lanthanum nitrate or ammonium metavanadate, and the molar ratio of the total amount of the auxiliary metal to the active substance metal is between 0.01-0.
15.
7. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 6, characterized in that: In B4, the mass ratio of the pickled carrier to the solution C is 1:3-5, the temperature of the resistance furnace is 600-700°C; zirconium beads are added inside the high-pressure reactor to prevent boiling during the heating process; The mass ratio of the zirconium beads to the carrier is 1:
20.
8. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 1, characterized in that: When the batch size of the target catalyst is less than 10 kg, the following steps are further included before step B5: B5': After the autoclave is cooled to room temperature, the catalyst precursor in the autoclave is taken out and placed in a halogen moisture analyzer for moisture testing, and the moisture content is controlled at 15-25%.
9. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 1, characterized in that: In B6, the catalyst precursor is calcined at 400-700°C for 2-8h, and the particle size of the target catalyst obtained after screening is 60-120 mesh; the catalyst with a particle size greater than 120 mesh obtained after screening is used for cracking LNG in a mobile fixed bed.
10. The method for preparing array carbon nanotubes using LNG as a carbon source according to claim 1, characterized in that: In C2, the fluidized bed reactor is heated to 650-700°C and 300 L / h N2 is introduced for 4-6 min; In C3, the reducing gas includes a mixed gas of 270 L / h N2 and 30 L / h H2, and the reduction reaction time is 0-20 min; in C4, the cracking gas includes a mixed gas of 210 L / h LNG and 60 L / h H2, and the cracking reaction time is 0.5-2 h.
Citation Information
Patent Citations
Method for preparing vermiculite-based catalyst, method for preparing carbon nanotubes, and catalyst and carbon nanotubes prepared therefrom
CN114632521A
Electrically conductive materials
CA3162482A1
Catalyst for fluidized bed preparation of carbon nanotube and preparation method of catalyst
CN104707615A
Ultrathin carbon NANO tube film and preparation method and apparatus thereof
WO2014180249A1
KR20240095634A
Cited By
Preparation method and application of catalyst for synthesizing multi-walled carbon nanotubes
CN121178175A
A method for preparing a catalyst for synthesizing multi-walled carbon nanotubes and its application.
CN121178175B